Environmental sustainability impacts of improper disposal of domestic pharmaceutical waste in the global south - Siti Hajar Mahamad Dom,; Hisyam Abdul Hamid,; Janattul Ain Jamal,; Ahmad Fauzi Dali,; Kamaliah Md Saman,; Norkasihan Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Improper pharmaceutical waste disposal is a rising environmental pollutant around the world. Pharmaceutical waste disposal legislation and regulations are available to some extent but limited to industrial premises and health-care institutions. Information on the disposal of pharmaceutical waste in public hands, known as domestic pharmaceutical waste (DPW), is limited. This scoping review aims to comprehend the global practice of DPW disposal by following the PRISMA Extension for Scoping Reviews guideline. Three online databases were searched for eligible articles: peer-reviewed in English language, describing the methods that the public disposed of unwanted or expired pharmaceuticals at home (DPW Disposal) and the public’s participation in their local DPW programs (DPW Program). Search terms were derived from Medical Subject Headings (MeSH) and free text when applicable. One expert report and thirty research publications were analysed. The articles originated from Asia (n=13), the Middle East (n=6), Africa (n=4), Europe (n=3), the United States (n=3) and Australia (n=1). Most pharmaceuticals are disposed of as household garbage (58.8%), returned to health facilities (17.9%) and flushed down the toilet drain (8.1%). There is a large range of diversity in public awareness (range: 14% - 82%) and participation in DPW Programs (range: 8.3% to 64%) with higher percentages reported from European countries. Existing regulations and policies have modest to moderate impact on proper DPW disposal. Our findings provide new information that may be utilised by policymakers in the process of laying the groundwork for a national plan outlining the most effective methods for disposing of DPW.